A novel device reduces anal pain after rubber band ligation: a randomized controlled trial - Lam, T. J. (Springer Milan, 2012)
BACKGROUND: Anal pain is a well-known sequel of rubber band ligation (RBL). A plastic device, the anal cooler which can be frozen in a freezer, has been developed to reduce anal pain. It contains a mixture of glycols and has a minimum temperature of 4 °C. This study was designed to investigate the efficacy of the anal cooler in pain relief after RBL. METHODS: Between 2009 and 2010, 100 patients who underwent RBL were prospectively randomized into an anal cooler group (n = 50) or a control group (n = 50). The anal cooler group was instructed to use the cooler when they had pain. All patients were asked to keep a pain diary (0 = no pain; 10 = extreme pain), and follow-up was performed after 3–6 weeks. RESULTS: It was found that 24/50 patients (48 %) in the anal cooler group and 31/50 (62 %) in the control group needed oral analgesics (NS). In total, 36/50 patients (72 %) used the anal cooler. Of these, 9/36 patients (25 %) noticed improvement. Of the remaining 27/36 patients (75 %) who did not notice improvement, 5/36 patients (14 %) found the insertion of the cooler uncomfortable and 1/36 patients (3 %) experienced nausea. No complications occurred during or after the use of the cooler. The 14/50 patients (28 %), who did not use the cooler, had a lower post-banding pain score compared with patients who used the cooler (1.4 vs 6.4; P < 0.001). CONCLUSIONS: Although post-banding pain after RBL is usually mild, the anal cooler seems to relieve anal pain in 25 % of the patients who used the device.